Faecal Myeloperoxidase as a Biomarker of Endoscopic Activity in Inflammatory Bowel Disease. (8th July 2022) - Swaminathan, Akhilesh; Borichevsky, Grace M; Edwards, Teagan S; Hirschfeld, Esther; Mules, Thomas C; Frampton, Chris M A; Day, Andrew S; Hampton, Mark B; Kettle, Anthony J; Gearry, Richard B
Abstract: Background and Aims: Inflammatory bowel disease [IBD], consisting of Crohn's disease [CD] and ulcerative colitis [UC], is a relapsing-remitting illness. Treat-to-target IBD management strategies require monitoring of gastrointestinal inflammation. This study aimed to investigate faecal myeloperoxidase [fMPO], a neutrophil granule enzyme, as a biomarker of IBD activity. Methods: Prospectively recruited participants with IBD, undergoing ileocolonoscopy for disease assessment, provided biological samples and completed symptom questionnaires prior to endoscopy. fMPO, C-reactive protein [CRP], and faecal calprotectin [fCal] were compared with validated endoscopic indices [simple endoscopic score for CD and UC endoscopic index of severity]. Receiver operating characteristic [ROC] curves assessed the performance of fMPO, CRP, and fCal in predicting endoscopic disease activity. Baseline biomarkers were used to predict a composite endpoint of complicated disease at 12 months [need for escalation of biologic/immunomodulator due to relapse, steroid use, IBD-related hospitalisation, and surgery]. Results: A total of 172 participants were recruited [91 female, 100 with CD]. fMPO was significantly correlated with endoscopic activity in both CD [r = 0.53, p  < 0.01] and UC [r = 0.63, p  < 0.01], and with fCal in all patients with IBD [r = 0.82, p  < 0.01]. fMPO was effective in predicting moderate-to-severely active CD [AUROC 0.86, p  < 0.01] and UC [AUROC 0.92, p  < 0.01]. Individuals with a baseline fMPO > 26 µg/g were significantly more likely to reach the composite outcome at 12 months (hazard ratio [HR] 3.71, 95% confidence interval [CI] 2.07–6.64, p  < 0.01). Conclusions: Faecal myeloperoxidase is an accurate biomarker of endoscopic activity in IBD and predicted a more complicated IBD course during follow-up. Graphical Abstract: